2016
DOI: 10.1177/1557988316652843
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lower Urinary Tract Symptoms Associated With Testosterone Replacement Therapy in Japanese Men With Late-Onset Hypogonadism

Abstract: This study aimed to investigate the effects of testosterone replacement therapy (TRT) on lower urinary tract symptoms (LUTS) in men with late-onset hypogonadism (LOH) and to identify parameters predicting the efficacy of TRT in improving LUTS. This study included 60 consecutive Japanese men who were diagnosed with LOH and subsequently received TRT between January 2009 and December 2014. In this series, 250 mg of testosterone was injected intramuscularly every 3 or 4 weeks in all patients. The following paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…T therapy improved LUTSs in men with TD and mild BPH [6768]. Okada et al [69] demonstrated that T therapy has considerable therapeutic benefits on LUTS in Japanese men with TD.…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…T therapy improved LUTSs in men with TD and mild BPH [6768]. Okada et al [69] demonstrated that T therapy has considerable therapeutic benefits on LUTS in Japanese men with TD.…”
Section: Benefits Of T Therapy In Men With Tdmentioning
confidence: 99%
“…This finding may imply that a deficiency of testosterone can widely affect the functions of multiple organs including psychological and physical systems [1]. SDS and AMS scale are frequently used to assess the severity of depression and LOH syndrome, respectively [7,12,13]. Since typical symptoms of LOH include depression, they are believed to be helpful for LOH screening [5,6,14].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to lower urinary tract symptoms (LUTS) in CKD patients, Chen et al (Chen, 2019) proposed bladder urothelial dysfunction, chronic inflammation, and change in sensory protein in the bladder urothelium as the mechanisms of bladder instability in patients with CKD and end-stage renal disease (ESRD). Some recent studies have reported that testosterone treatment improved LUTS (Okada et al, 2018; Yucel et al, 2017). Although more research is necessary on LUTS in CKD patients with TD, the opinion stated in the current guidelines is that in general, testosterone treatment does not greatly affect LUTS induced by BPH (Bhasin et al, 2018; Morgentaler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%